Profiles of Language and Behavior in Students With Emotional Disturbance. (August 2019) - Hollo, Alexandra; Chow, Jason C.; Wehby, Joseph H.
Although global associations between language and behavioral development are well established, relations among components and subgroups within these disorders remain unclear. The primary aim of this study was to explore whether language components differed by behavioral subtypes: internalizing only, externalizing only, or both. To control for confounding factors identified in prior studies related to sampling and measurement, we conducted profile analyses of receptive, expressive, pragmatic, semantic, syntactic, or higher order language skills in 46 boys with emotional disturbance (ED) using one comprehensive language measure. On average, the internalizing-only group outperformed all other behavioral subgroups. Absence of interaction effects indicated similar patterns of performance, with all groups performing lowest in pragmatic language. We also report prevalence rates of language deficits in the sample and analyze results using two different grouping strategies. Discussion includes the importance of considering comorbidity and establishing independent behavioral subgroups in research, as well as implications for assessment and intervention in practice.